2018
DOI: 10.1111/jvh.13027
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone levels by presence and severity of cirrhosis in women with chronic hepatitis C virus infection

Abstract: Summary Cirrhosis is associated with hormonal dysregulation, as evidenced by secondary amenorrhoea in reproductive‐aged women, and feminization of cirrhotic men. Whether hormone levels vary by severity of cirrhosis in women is not known. If identified, such changes may have important clinical relevance, particularly, as low sex hormone binding globulin (SHBG) and follicle stimulating hormone (FSH) are known to promote metabolic and cardiovascular disease in women. In a cohort of post‐menopausal women with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Studies of HCV-infected individuals reported that SHBG levels were positively associated with severity of liver disease in men, (37) but this association was not observed in women. (38) However, it has been hypothesized that SHBG may be a marker of liver damage. The mechanism underlying this correlation between SHBG and liver damage has been suggested to be through insulin-like growth factor 1 (IGF-1), which down-regulates SHBG production.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of HCV-infected individuals reported that SHBG levels were positively associated with severity of liver disease in men, (37) but this association was not observed in women. (38) However, it has been hypothesized that SHBG may be a marker of liver damage. The mechanism underlying this correlation between SHBG and liver damage has been suggested to be through insulin-like growth factor 1 (IGF-1), which down-regulates SHBG production.…”
Section: Discussionmentioning
confidence: 99%
“…Since testosterone directly modulates osteoblasts and osteocytes via the androgen receptor to stimulate trabecular bone formation and prevent its loss, low testosterone level owing to hypogonadism in male enhances osteoclast function and induces bone turnover [ 53 , 90 ]. Though estrogen levels are increased in patient with liver cirrhosis due to increased peripheral conversion of androgen to estrogen, altered estrogen metabolism in liver cirrhosis contributes to a decrease in degradation of estrogen metabolites [ 91 ]. Because the bone protective effect of these estrogens is weak, it is not enough to overcome post-menopausal osteoporosis in women and liver-disease related osteoporosis in men [ 92 , 93 ].…”
Section: Osteoporosis In Chronic Liver Diseasementioning
confidence: 99%
“…( 13‐15 ) Produced in the liver, SHBG synthesis is stimulated by estrogens, although with further progression from compensated to decompensated cirrhosis, SHBG levels ultimately decline. ( 16,17 ) Estrogen levels are also elevated in the setting of portosystemic shunting, ( 10,18 ) and increased circulating levels suppress the hypothalamic‐pituitary axis, ( 19 ) contributing to erectile dysfunction, oligospermia, testicular atrophy, and feminization. ( 20 )…”
Section: Sexual Function Across Age In Patients With Chronic Liver DImentioning
confidence: 99%